Human Liver Stem Cells: A Liver-Derived Mesenchymal Stromal Cell-Like Population With Pro-regenerative Properties - Bruno, Stefania; Herrera Sanchez, Maria Beatriz; Chiabotto, Giulia; Fonsato, Valentina; Navarro-Tableros, Victor; Pasquino, Chiara; Tapparo, Marta; Camussi, Giovanni (Frontiers in Cell and Developmental Biology, 2021)
Human liver stem cells (HLSCs) were described for the first time in 2006 as a new stem cell population derived from healthy human livers. Like mesenchymal stromal cells, HLSCs exhibit multipotent and immunomodulatory properties. HLSCs can differentiate into several lineages under defined in vitro conditions, such as mature hepatocytes, osteocytes, endothelial cells, and islet-like cell organoids. Over the years, HLSCs have been shown to contribute to tissue repair and regeneration in different in vivo models, leading to more than five granted patents and over 15 peer reviewed scientific articles elucidating their potential therapeutic role in various experimental pathologies. In addition, HLSCs have recently completed a Phase 1 study evaluating their safety post intrahepatic injection in infants with inherited neonatal onset hyperammonemia. Even though a lot of progress has been made in understanding HLSCs over the past years, some important questions regarding the mechanisms of action remain to be elucidated. Among the mechanisms of interaction of HLSCs with their environment, a paracrine interface has emerged involving extracellular vesicles (EVs) as vehicles for transferring active biological materials. In our group, the EVs derived from HLSCs have been studied in vitro as well as in vivo. Our attention has mainly been focused on understanding the in vivo ability of HLSC–derived EVs as modulators of tissue regeneration, inflammation, fibrosis, and tumor growth. This review article aims to discuss in detail the role of HLSCs and HLSC-EVs in these processes and their possible future therapeutic applications.